Application of chromosomal microarray in the evaluation of abnormal prenatal findings. (4th November 2012) - Yatsenko, SA; Davis, S; Hendrix, NW; Surti, U; Emery, S; Canavan, T; Speer, P; Hill, L; Clemens, M; Rajkovic, A
<x xml:space="preserve">Abstract</x> We performed karyotype and array comparative genomic hybridization (aCGH) analyses on 177 prenatal samples, including 162 (92%) samples from fetuses with sonographic anomalies. Overall 12 fetuses (6.8%) had abnormal karyotype and 42 (23.7%) fetuses had abnormal microarray results: 20 (11.3%) with pathogenic copy number variations (CNVs), 16 with CNVs of uncertain clinical significance, 4 with CNVs establishing carrier status for recessive, X‐linked, or susceptibility to late onset dominant disease, and two CNVs with pseudomosaicism due to in vitro cultural artifacts. For 23 pregnancies (13%), aCGH contributed important new information. Our results highlight the interpretation challenges associated with CNVs of unclear significance, incidental findings, as well as technical aspects. Array CGH analysis significantly improved the detection of genomic imbalances in prenatal diagnosis of pregnancies with structural birth defects.